1994
DOI: 10.1084/jem.179.5.1445
|View full text |Cite
|
Sign up to set email alerts
|

Human rheumatoid factors with restrictive specificity for rabbit immunoglobulin G: auto- and multi-reactivity, diverse VH gene segment usage and preferential usage of V lambda IIIb.

Abstract: SummaryTo determine the molecular and functional properties of human rheumatoid factors (RF), we established stable hybridomas and Epstein-Barr virus-transformed B cell lines from the synovial fluid or peripheral blood of three patients with rheumatoid arthritis and one patient with systemic lupus erythematosus. 17 cell lines were obtained that produced high-titer immunoglobulin M (IgM) RF that reacted exclusively with rabbit but not human IgG or IgG of other mammalian species. Certain anti-rabbit IgG RF also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…This indicates a selective expansion of 3 RF B cells subset in pSS. Fang et al 1994 also found a preferential utilization of V 3b family genes among some RFs with specificity for rabbit IgG obtained from the synovial fluid or peripheral blood of patients with RA [32]. In contrast, only two of our V 3 RFs were reactive with the rabbit IgG [16].…”
Section: Rheumatoid Factor Light Chain In Pss 495mentioning
confidence: 78%
“…This indicates a selective expansion of 3 RF B cells subset in pSS. Fang et al 1994 also found a preferential utilization of V 3b family genes among some RFs with specificity for rabbit IgG obtained from the synovial fluid or peripheral blood of patients with RA [32]. In contrast, only two of our V 3 RFs were reactive with the rabbit IgG [16].…”
Section: Rheumatoid Factor Light Chain In Pss 495mentioning
confidence: 78%
“…Several recent studies have shown that V H genes used in natural autoantibodies are those preferentially expressed or utilized during fetal development, and rearrangements of these natural autoantibodies are mostly unmutated [8,17,18,31,32,49]. In contrast, V H gene usage in IgM RF from peripheral blood of RA patients has been shown to be genetically heterogeneous and somatically mutated [21,22]. Further, an elevation of somatic hypermutation has been observed in CDRs of V H and V L in two of three IgG RF [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact mechanisms involved in the pathologic autoantibody response in RA remain unclear. Studies of antibody structure may help to decipher the aetiology of a potentially pathologic autoantibody response in RA [8][9][10][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that in this patient, emergence of Vcontaining autoantibodies during B cell ontogeny may have been the stimulus for central V receptor editing. In this context, V genes are a critical part of a number of human autoantibodies, including antibodies to dsDNA, to La/SSB and Ro/SSA, to laminin, to phospholipids, to collagen, and to histone 2A and rheumatoid factor (RF) (60,(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73)(74).…”
Section: Receptor Editing and Autoimmunitymentioning
confidence: 99%